Tru love [videorecording (DVD)] - Johnston, Kate (Director); Macdonald, Shauna, 1981-; Trotter, Kate; Horne, Christine, 1981-; Chapman, Alexander, 1976- (Wolfe Video, 2014)
Tru, a 37-year-old bed-hopping lesbian, becomes unexpectedly smitten with elegant 60-year-old Alice. As their affection deepens, Alice's daughter Suzanne worries that Tru may break her mother's heart. But it seems this lesbian Casanova may have found true love at last.